Eksistensi AAUPB di Indonesia dan Yurisprudensinya Dalam Perkara TUN - Ikhsan Fatah Yasin (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
This article discusses the General Principles of Good Governance (AAUPB). It has a long journey from the beginning of its coming in the Netherland to its application in Indonesia today. AAUPB, which previously was only in theoretical realm, it changes into Law No. 30 of 2014 today. The principles contained in the law are legal certainty; expediency; impartiality; accuracy; not to abuse authority; openness; public interest; and good service. In addition to these principles, we can also use other principles as far as they become the basis for the judges' judgments that have permanent legal force. In various cases, the basis of the claim of AAUPB does not stand alone but it is also juxtaposed with violations of statutory regulations. The Supreme Court verdict has become a jurisprudence between Suhaili Saun (shareholder in PT Volex Batamindah) and the Chairman of BKPM, although the plaintiff also argued that violating the AAUPB namely the principle of legal certainty, the defendant also violated article 2 letter b of Law No. 1 of 1967 about Foreign Investment. In the case of the dismissal of Bripda Helga Musa Sitepu by the Head of the North Sumatra Regional Police, the decree has violated article 2 paragraph 2 letter d and article 11 paragraph 1 of KAPOLRI regulation No. 8 of 2006 and was contrary to the principle of the district.